Multidisciplinary inpatient rehabilitation for older adults with COVID-19: a systematic review and meta-analysis of clinical and process outcomes - Aoife McCarthy; Rose Galvin; Frances Dockery; Kara McLoughlin; Margaret O’Connor; Gillian Corey; Aoife Whiston; Leonora Carey; Fiona Steed; Audrey Tierney; Katie Robinson (BMC Geriatrics, 2023)
Abstract Background Older adults are at increased risk for disease severity and poorer prognosis following COVID-19 infection. The aim of this systematic review and meta-analysis is to explore the impact of multidisciplinary rehabilitation in the acute or post-acute hospital setting for older adults with COVID-19. Methods The Cochrane library, EMBASE, Cinahl and Medline (via EBSCO), PubMed, and Web of Science were systematically searched in June 2022 and a repeat search was completed in March 2023. Screening, data extraction and quality appraisal were conducted independently by two reviewers. Studies reporting outcomes for older adults following multidisciplinary rehabilitation (provided by two or more Health and Social Care Professionals) were included. Both observational and experimental study designs were included. The primary outcome was functional ability. Secondary outcomes included discharge disposition, acute hospital and rehabilitation unit length of stay, mortality, primary and secondary healthcare utilisation, and long-term effects of COVID-19. Results Twelve studies met the inclusion criteria, comprising a total of 570 older adults. Where reported, older adults stayed in the acute hospital for a mean of 18 days (95%CI, 13.35- 23.13 days) and in rehabilitation units for 19 days (95%CI, 15.88–21.79 days). There was a significant improvement in functional ability among older adults with COVID-19 who received multidisciplinary rehabilitation (REM, SMD = 1.46, 95% CI 0.94 to 1.98). The proportion of older adults who were discharged directly home following rehabilitation ranged from 62 to 97%. Two studies reported a 2% inpatient mortality rate of older persons during rehabilitative care. No study followed up patients after the point of discharge and no study reported on long term effects of COVID-19. Conclusions Multidisciplinary rehabilitation may result in improved functional outcomes on discharge from rehabilitation units/centres for older adults with COVID-19. Findings also highlight the need for further research into the long-term effect of rehabilitation for older adults following COVID-19. Future research should comprehensively describe multidisciplinary rehabilitation in terms of disciplines involved and the intervention provided.